Sistem Absensi Dosen Berbasis Radio Frequency Identification (RFID) Sebagai Perhitungan Honor Dosen - Muhammad Ikhwan Mardin; Andani Ahmad; Wardi Wardi (Universitas Darul Ulum, 2024)
This research designed a sense to find out the number of lecturers who enter and finish teaching lectures. Fikom, UMI still uses a manual system in managing lecturers' teaching salaries, so that it has several battles that usually occur in manual systems, including the attendance process and attendance recapitulation inefficient, less transparent because lecturers cannot access the issue of honorarium that lecturers will receive, and what will happen is that the salary calculation is not accurate so that it often results in disputes between lecturers and the finance department. on this occasion the author tries to design a working system of a tool that can recap lecturer attendance that can function to increase efficiency, transparency, and accuracy in the management of lecturer teaching honoraria. The system designed in this study was made using the RFID module and Raspberry Pi as the primary component of the system. The original way of working of this system comes from reading identification data from the RFID card carried by the lecturer. The data read by the RFID will be sent to the Raspberry Pi as input data. Raspberry pi will send RFID data readings to the server computer into input data. personal computer server will get data from Raspberry pi and will check the data, when the data received is synchronized with the ongoing course schedule, the server computer will send the data to Raspberry and will be displayed on the LCD. which will occur from this research shares that the process of computerized honorarium management tends to be easier and management has a better level of accuracy than using manual methods. in terms of news, reports that are designed tend to be simpler and faster because they are automatically in accordance with the input data entered previously.